Efektivitas Tata Letak Gudang dengan Metode First In First Out (FIFO) pada PT. Sari Warna Asli Garment Solo - Halimatuss Sa Diyah; Yusi Rahmawati; Iik Suryati (Journal of Research and Development on Public Policy, 2026)
This research is motivated by the importance of an effective warehouse layout in supporting smooth inventory flow and stable production operations. The implementation of the First In First Out (FIFO) method is seen as a key strategy to prevent stock buildup, reduce the risk of material deterioration, and improve inventory management efficiency. The purpose of this study is to determine the effectiveness of the FIFO-based warehouse layout at PT. Sari Warna Asli Garment Solo and identify the factors that influence it. This study uses a descriptive qualitative approach located in the raw material warehouse. Data were obtained through interviews, intensive observation for four months, documentation, and document analysis, then systematically analyzed based on themes. The results show that the FIFO implementation runs quite well through date-of-entry marking, grouping of goods, and arrangement of storage zones, thus accelerating stock turnover and minimizing buildup. However, inconsistencies were still found during high workloads and limitations in the integration of manual and digital recording. It is concluded that the FIFO-based warehouse layout is effective, but requires strengthening work discipline, regular evaluation, and information system development.